Societal Change Systems: A Framework to Address Wicked Problems. (December 2016) - Waddell, Steve
Problems referred to as wicked, messy, complex, and meta-level, by their very nature, require involving multiple and diverse organizations. Issues such as climate change, poverty, sustainable agriculture, and health care involve many hundreds of organizations at a national level; at a global level this easily increases to many thousands. Emerging their collective power into an effective force represents an enormous organizing challenge. Drawing from complexity and global networking knowledge, and building on the concept of "innovation system, " this article develops the concept of "societal change system" as a framework to support addressing the organizing challenge. This arose through analysis of global change initiatives aiming to integrate sustainability concerns into the production of electricity, which included a meeting of leaders of such change initiatives. The activities produced recommendations for greatly enhancing change efforts with pragmatic steps to develop the societal change system in which they are embedded.